Spatial-Temporal Variations and Influencing Factors of Water-related Ecosystem Services in Southwest China Under Complex Terrain - TANG Shuang; ZHU Chongjing; GAO Jie; BIAN Hongyan (Shuitu Baochi Xuebao)
[Objective] The study of spatial-temporal variations and influencing factors of water-related ecosystem services under complex terrain in Southwest China can serve as a foundation for the ecological management and sustainable development in this region. [Methods] The annual water yield and soil erosion in Southwest China from 1992 to 2020 were evaluated to explore the multi-dimensional (including time, space and elevation) variation characteristics by the InVEST model and universal soil loss equation. In addition, the relative weight analysis method was used to quantify the relative contribution rate of climate and land use change to water-related ecosystem services. [Results] (1) From 1992 to 2020, water yield in Southwest China showed a downward trend, with a notable mutation occurring in 2002; soil erosion showed an increasing trend, with a mutation observed in 1997. (2) The water yield decreased and soil erosion increased with rising altitude. (3) The relative contribution rate of precipitation to both water yield and soil erosion in karst areas was found to be greater than that in non-karst areas. [Conclusion] Climate change has a more significant impact on water yield and soil erosion, while land use change has a less obvious impact. This study will contribute to the ecological protection in complex terrain (with different elevations and different landforms) and provide a scientific basis for land management and ecological restoration measures in karst areas.